2021
DOI: 10.1186/s12872-021-01913-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and its relations to conventional risk factors for cardiovascular diseases in adult Nigerians: the REMAH study

Abstract: Background Evidence linking homocysteine (Hcy) with cardiovascular diseases (CVD) or its risk factors are limited in a sub-Saharan black population. Objective We set out to evaluate the association between Hcy and hypertension and other CVD risk factors in a population of adult Nigerians. Methods Data of 156 adults aged 18–70 years was accessed from the North Central study site of the REmoving the MAsk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…There were also some invaluable clinical observations that demonstrated the possible link between Hcy and lipid metabolism pathways. Consistent research findings suggest that Hcy is significantly and negatively correlated with HDL-C and ApoAI in community-based or health physical examination populations, [12–17] and these correlations also exist in patients with diagnosed CAD. [19–21] It is well known that HDL and ApoAI exert antiatherogenic effects by transporting cholesterol from cells into peripheral tissues, [32] reducing oxidative stress and suppressing inflammatory pathways.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There were also some invaluable clinical observations that demonstrated the possible link between Hcy and lipid metabolism pathways. Consistent research findings suggest that Hcy is significantly and negatively correlated with HDL-C and ApoAI in community-based or health physical examination populations, [12–17] and these correlations also exist in patients with diagnosed CAD. [19–21] It is well known that HDL and ApoAI exert antiatherogenic effects by transporting cholesterol from cells into peripheral tissues, [32] reducing oxidative stress and suppressing inflammatory pathways.…”
Section: Discussionmentioning
confidence: 81%
“…HHcy acts through various mechanisms, including vascular endothelial damage, stimulation of smooth muscle cell proliferation, and thrombosis activation. [10,11] Previous studies have shown that HHcy and serum Hcy are positively correlated with serum TC, LDL-C, and TG levels [12,13] and negatively correlated with serum HDL-C [12–17] and ApoAI [17] levels in physical examination populations or community-based populations. However, the VLDL-21 study [18] failed to find an association between HHcy and lipid profiles in a large population.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the number of deaths associated with CVDs will increase from 17.5 million to 25 million by 2030 [3]. Lipid profiles are studied or tested in hospitals or by researchers to detect the risk of heart disease or cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma total homocysteine (tHcy) is primarily considered to be a biomarker of functional vitamin B12 and folate status, and has also been demonstrated to be useful as a general risk marker of cardiovascular disease (CVD) [1,2]. tHcy is associated with cardiovascular risk factors [3] and correlates with the Framingham cardiovascular risk score [4]. Smoking is one of the strongest established risk factors for CVD.…”
Section: Introductionmentioning
confidence: 99%